A representação temática da literatura de Cordel à luz da teoria dos campos lexicais - Paiva, Andréia Del Conte de (2023)
Cordel literature has undeniable importance to society, whether as a historical document, source of information, entertainment, means of communication or scientific research. Registries of memory, of the social, political and economic trajectory of the Brazilian people, this is a literary genre that establishes itself as a significant instrument in the teaching and learning process in various areas of knowledge. Due to their characteristics, the range of contexts of use and the degree of acceptance by different types of readers, the need arises to organize them. In this sense, Information Science (CI) is evident which, through the Thematic Treatment of Information, enables access to these literary works. From this perspective, the guiding question of the research on screen is characterized as how to provide professionals in the Area with conditions to efficiently represent the cordel leaflets. Representing to organize these materials constitutes a process of expressive complexity. The information skills inherent in the Thematic Treatment of Information process, required of information professionals, among other aspects, reinforce the hypothesis that the design of the classification of leaflets based on the twenty-seven thematic classes proposed by Albuquerque (2011), as well as the Theory of Lexical Fields, will contribute to the organization and access to these materials. Aiming to apply the Theory of the Lexical Field regarding the Thematic Treatment of Information in cordel literature. The methodological course was carried out by a qualitative study, with descriptive exploratory objectives using the action-research procedure. This work is justified due to the scarcity of studies related to the theoretical and methodological construction for the representation of the informational content of the leaflets, contributing with information professionals to the thematic treatment of the cordel leaflets.